IMPLEMENTATION OF PROVIDING LEGAL AID TO CHILDREN AS PERPETRATORS OF THE CRIME OF OBSCENITY - Larasati, Shindy Cika; Yustrisia, Lola; Munandar, Syaiful (DE'RECHTSSTAAT, 2024)
Legal aid is a right of the poor that can be obtained without payment (probono public). The provision of legal aid has also been regulated in Article 23 paragraph (1) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which emphasizes that legal aid is an obligation given from the state for children of criminal offenders since being arrested or detained and during the time of examination. The problems that the authors examine in this study are 1). How is the implementation of the provision of legal assistance to children as perpetrators of criminal acts of sexual immorality at Posbakum PN Bukittinggi, 2). What are the Obstacles Faced in the Implementation of Providing Legal Assistance to Children as Perpetrators of the Criminal Act of Obscenity at Posbakum PN Bukittinggi, 3). What Legal Remedies Can Be Taken To Overcome Obstacles That Occur In The Implementation Of Giving Law To Children As Perpetrators Of Criminal Obscene Acts By Posbakum PN Bukittinggi. The research method that the writer uses is empirical legal research. Therefore it can be concluded 1). The implementation of the provision of legal assistance to children as perpetrators of criminal acts of obscenity by the Bukittinggi Legal Aid Institute has been carried out in accordance with procedures and has permanent legal force. 2). The obstacles faced in the implementation of the provision of legal aid by the Bukittinggi Legal Aid Institute were in the form of Legal Aid Funding Arrangements, the lack of witnesses presented, Using a Visum Et Repertum Letter. 3). Efforts to overcome obstacles in the provision of legal aid by the Bukittinggi Legal Aid Institute in the form of the Government need to pay attention to the implementation of legal aid for the poor, There is a need for updating the Law regarding witness statements, because in this case the perpetrators and victims are minors, and the the legal aid provider feels that the Visum Et Repertum must be carried out as soon as possible before the marks disappear.